DIFFICULTIES FACED BY MIDDLE SCHOOL STUDENTS IN ENGLISH PRONUNCIATION - Putri Jum’ati Praistiana; Raden Agus Budiharto (Universitas Madura, 2020)
Pronunciation for students is one of the important parts in learning English. The students often find a problem with pronunciation when they speak, read, or listen in English word. They still have poor pronunciation. It can be seen in the daily teaching and learning process, especially in speaking class. It is difficult for the students to pronounce English words. The problem was most of the student’s pronunciation was likely to be influenced by their first language., in this case, madurase language. This research aims to investigates two problems which become the main discussion of this research. The first is to describe students difficulties in English pronunciation and to know the solution of students difficulties in English pronunciation. This research is qualitative research by using descriptive case study. The participant of this research are students in first grade of SMP Negeri 2 Kedungdung. the data were collected by using observation and some interview between the researcher and students, and also the researcher and the teacher. The result of this research showed that the word difficult to pronunciation by students is “wanted” and “remembers”. All of the students make mispronunciation in “wanted” and 16 students make mispronunciation in “remembers” word. The factors students difficult to pronounce English word is the different between lettering and pronouncing, English in not their mother tongue, and the students did not practice English in their daily activity. The possible solution from the researcher to resolve the students difficulties in English pronunciation: the teacher can give motivation to the students about English is interesting to study, the students can listening English music and practice it, and the teacher make strategies to teach English lessons that make students interesting to study.